Opus Imperfectum - A Mixed Reality Concert About the Origin of Life - de Carvalho, Alyson Matheus; Campos, Cleber Da Silveira; Rennó-Costa, César (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2023)
This paper explores the integration of Virtual Reality (VR) technology in concerts, focusing on creating immersive experiences through Mixed Reality (MR) environments. By combining generative graphics, projections, and VR elements, the audience’s concert experience can be enriched and aligned with the artists’ performances and themes. The Opus Imperfectum MR experience, featuring a musical composition with four acts portraying the journey of life on Earth, exemplifies how MR can augment concert exhibitions and engage audiences in a dynamic and educational manner. The paper outlines the development process of the MR experience and discusses opportunities for further exploration of this technology.